The relationship between job demands, job resources and work engagement among administrative staffs in public university - Nur Hidayah, Othman (2016)
Work engagement become very crucial in today's organization. There are quite number of organizations which are strive and implement work engagement in their workplace environment. Hence this study investigates the relationship between Job Demands (workload, work pressure), Job Resources (autonomy and supervisor support) and work engagement. A total of 200 questionnaires was personally distributed to respondents from 9 faculties of administrative staffs in Universiti Pendidikan Sultan Idris (UPSI) which in charge of students. Out of 200 questionnaires distributed, only 178 were returned, representing a response rate of 89.5%. Hypotheses for the relationship were tested using multiple regression analyses. Results showed that work pressure, autonomy and supervisor support was significantly positive related to work engagement. Implications of the findings, potential limitations, and directions for future research are discussed.